Introducción para un estudio sobre la relación de Josemaría Escrivá de Balaguer con el Real Patronato de Santa Isabel de Madrid / Introduction to a study on the relationship between Josemaría Escrivá and the Real Patronato de Santa Isabel in Madrid - Beatriz Comella Gutiérrez (Studia et Documenta)
The following study is made up of three closely related parts: firstly, the ties between St. Josemaría Escrivá and the Real Patronato de Santa Isabel, during the years 1931 to 1945, initially as acting chaplain and later on, as rector and administrator; secondly, it presents a documented history of the Real Patronato, a religious and educational trust founded by Philip II; and finally, available sources are listed for further studies regarding the founder of Opus Dei and the Real Patronato de Santa Isabel.